2015
DOI: 10.1007/7854_2015_428
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific Interactions in Adult Laboratory Rodents: Friends or Foes?

Abstract: Interactions between adult conspecifics, including sexual behaviors, affiliation, and aggression are crucial for the well-being, survival, and reproduction of mammals. This holds true for any mammalian species, but certainly for humans: An inability to optimally navigate the social system can have a strong negative impact on physical and mental health. Translational rodent models have been used for decades to unravel the neural pathways and substrates involved in normal and abnormal conspecific interactions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…In detail, the display of high aggression by IST females during the FIT was accompanied by elevated OXT release within the vLS, which was also reflected by higher OXT levels in their CSF. Together with the fact that central OXT release correlated with aggression, this indicates the involvement of septal OXT in the high aggression displayed by IST rats, which we further confirmed by complementary pharmacological, chemogenetic and optogenetic approaches: OXT and AVP have been repeatedly described as important neuromodulators of social behaviors in rodents, acting either synergistically or antagonistically depending on the social context and sex 8,9,22,24,36,43 . In males, reduced aggression has been reported in rats after i.c.v.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In detail, the display of high aggression by IST females during the FIT was accompanied by elevated OXT release within the vLS, which was also reflected by higher OXT levels in their CSF. Together with the fact that central OXT release correlated with aggression, this indicates the involvement of septal OXT in the high aggression displayed by IST rats, which we further confirmed by complementary pharmacological, chemogenetic and optogenetic approaches: OXT and AVP have been repeatedly described as important neuromodulators of social behaviors in rodents, acting either synergistically or antagonistically depending on the social context and sex 8,9,22,24,36,43 . In males, reduced aggression has been reported in rats after i.c.v.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, the few studies on OXT-effects on female aggression rather revealed pro-aggressive or antisocial effects, for example in female rhesus monkeys 44 , non-lactating women 8,45 , and in lactating female rats 18,33 . Although the factors motivating the display of aggression and its severity likely differ in lactating versus virgin females 5,33,46,47 , we should highlight that from an evolutionary point of view, co-opting the same neuropeptidergic systems for promoting aggression in lactating females to protect the offspring, and in virgin females to protect their territory, or to get access to resources, makes sense; especially knowing that high activity of the brain OXT system reflected by elevated neuropeptide synthesis, release and binding 18,24,33,36 is known to underlie maternal aggression 24,33,36,48 . Further evidence for a sex-specific effect of OXT on social behavior comes from studies on social motivation, where OXT is essential for naturally occurring social preference behavior in male rats and mice , but not in virgin female rats 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its role in pair bonding, OT is released centrally during pro-social interactions thereby regulating other social behaviors, e.g., social recognition, social memory, parental behavior, as mainly demonstrated in rodents (Bosch and Neumann 2012; Lukas and Neumann 2013; Dumais and Veenema 2016; Lukas and de Jong 2017). In male and female prairie voles, OT acting on the anterior cingulate cortex, a region implicated in empathy in humans (Lamm et al 2011), regulates empathy-based consoling behaviors (Burkett et al 2016).…”
Section: Oxytocin and Other Social And Stress-related Behaviorsmentioning
confidence: 99%